2018
DOI: 10.3389/fimmu.2018.00365
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B5 Reduces Bacterial Growth via Regulating Innate Immunity and Adaptive Immunity in Mice Infected with Mycobacterium tuberculosis

Abstract: The mechanisms by which vitamins regulate immunity and their effect as an adjuvant treatment for tuberculosis have gradually become very important research topics. Studies have found that vitamin B5 (VB5) can promote epithelial cells to express inflammatory cytokines. We aimed to examine the proinflammatory and antibacterial effect of VB5 in macrophages infected with Mycobacterium tuberculosis (MTB) strain H37Rv and the therapeutic potential of VB5 in vivo with tuberculosis. We investigated the activation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 32 publications
2
52
0
1
Order By: Relevance
“…Probiotic bacteria, members of the gut microbiota, are able to synthesize panthotenic acid in humans (Hill, ). VB5 helps the body to build an effective immune response to resist infection (He et al, ). Several genes encoding VB5 biosynthesis have been implicated as potential causal factors for campylobacter‐associated gastroenteritis in cattles.…”
Section: Vb5 and Wounds (Stitches)mentioning
confidence: 99%
See 3 more Smart Citations
“…Probiotic bacteria, members of the gut microbiota, are able to synthesize panthotenic acid in humans (Hill, ). VB5 helps the body to build an effective immune response to resist infection (He et al, ). Several genes encoding VB5 biosynthesis have been implicated as potential causal factors for campylobacter‐associated gastroenteritis in cattles.…”
Section: Vb5 and Wounds (Stitches)mentioning
confidence: 99%
“…It promotes the maturity of macrophages and increases differentiation of Th1 and Th17 cells (Berruyer et al, ; van Diepen et al, ; Xu, Wang, Gao, & Liu, ). A proinflammatory and antimicromial action of VB5 in macrophages infected with Mycobacterium tuberculosis has been reported (He et al, ). Such antimicrobial action may pave way for future roles of VB5 in various organs and tissues including the skin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even when they are produced, concentrations are low and external supplementation from the diet or from commensal bacteria is required. Vitamins have been found to regulate immunity, and a number of studies have reported the effect of vitamins as adjunct to treat tuberculosis (Parida et al, 2015;He et al, 2018). For example, vitamins A, C and D have been used as adjunct to complement anti-tuberculosis drugs (Dini and Bianchi, 2012;Vilcheze et al, 2013;Syal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%